2014
DOI: 10.4103/2230-8210.131211
|View full text |Cite
|
Sign up to set email alerts
|

Our experience with papillary thyroid microcancer

Abstract: Background:Papillary thyroid microcarcinoma (PTMC) describes a focus of papillary thyroid cancer that is less than 1 cm in size. These tumors are frequently found on histopathological examination of thyroid specimens, operated upon for an indication other than suspected malignancy.Materials and Methods:From 2005 to 2012, 94 of 1300 thyroidectomy specimens in our institution were found to have PTMC. Of these, 77 were isolated PTMC while the others were associated with other differentiated cancers. We studied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…Our incidence rate of 18% for the presence of two or more foci in the gland and the rate of 20% for the location of tumour foci in both lobes confirmed the pathological features of incidental PTM. Previous studies have also reported the multifocality rate of I-PTM to be between 13% and 44.1% [ 7 – 9 , 15 – 19 ]. Some studies have reported multifocality as an independent risk factor for tumour recurrence [ 6 , 8 , 11 , 14 , 18 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our incidence rate of 18% for the presence of two or more foci in the gland and the rate of 20% for the location of tumour foci in both lobes confirmed the pathological features of incidental PTM. Previous studies have also reported the multifocality rate of I-PTM to be between 13% and 44.1% [ 7 – 9 , 15 – 19 ]. Some studies have reported multifocality as an independent risk factor for tumour recurrence [ 6 , 8 , 11 , 14 , 18 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 97%
“…In another study, the proportion of PTM in papillary thyroid cancer cases was determined to be 49%, of which 58% were incidental [ 8 ]. The proportion of incidental cases among all PTM cases was found to be between 49% and 75.5% [ 8 , 11 15 ]. Londero et al [ 5 ] recently reported that age-standardised rates increased from 0.35 per 100,000 per year in 1996 to 0.74 per 100,000 per year in 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning associated thyroid diseases, multinodular goiter appear to have the highest incidence, from 4% to 17% (43,44). In Graves, the incidence varies from 0.5% to 1.8% (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…In this particular study, the authors observed the patients for approximately 180 months. Many researchers have emphasized the disadvantage of leaving thyroid tissue in the operative bed after subtotal thyroidectomy [2124]. They have suggested that in the future, some of these patients may require reoperation due to ITC in recurrent goiter, which may be associated with a worse prognosis and a higher rate of complications compared with patients who have received primary surgery [21–23].…”
Section: Introductionmentioning
confidence: 99%
“…They have suggested that in the future, some of these patients may require reoperation due to ITC in recurrent goiter, which may be associated with a worse prognosis and a higher rate of complications compared with patients who have received primary surgery [21–23]. John et al [24] examined 1300 thyroidectomy specimens for the presence of incidental papillary thyroid microcarcinoma. These authors noted that the most common indication for surgery among this group of patients was MNG with consideration of the ITC prevalence.…”
Section: Introductionmentioning
confidence: 99%